Kuwait : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2012)
This Selected Issues and Statistical Appendix paper on Kuwait focuses on recent development in investment companies (ICs) and the business environment in the country. ICs continue to be vulnerable to swings in financial and real estate markets. They continue to have large exposures to domestic, regional, and international equity and real estate markets. Local banks' lending to ICs declined in 2010-11 owing to banks' write-offs of ICs loans. The financial situation of many ICs remains precarious, and there are 15 listed investment companies in a dire situation.